2021
DOI: 10.17576/jsm-2021-5012-14
|View full text |Cite
|
Sign up to set email alerts
|

Poorer Attainment of Hemoglobin A1C, Blood Pressure and LDL-Cholesterol Goals among Younger Adults with Type 2 Diabetes

Abstract: Concurrent attainment of glycated haemoglobin A1C, blood pressure, and LDL-cholesterol goals, or collectively known as the ‘ABC’ goals, help prevent cardiovascular complications in patients with type 2 diabetes (T2D). We aimed to determine the proportion of T2D patients who achieved all three ABC goals in Malaysia’s public health clinics. We also determined the association between age groups with the attainment of all the ABC goals. A cross-sectional analysis of the baseline findings from a retrospective open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Some of our patients had young-onset T2D, which was associated with higher risks of mortality, macrovascular, and microvascular complications 14 , 23 . Previous Malaysian studies found that younger adults with T2D had poorer control of HbA1c, BP, and LDL-cholesterol 24 , 25 . Thus, there is a need to intensify metabolic control among this subpopulation to prevent adverse outcomes, especially after accounting for the legacy benefits of multifactorial risk interventions 26 .…”
Section: Discussionmentioning
confidence: 89%
“…Some of our patients had young-onset T2D, which was associated with higher risks of mortality, macrovascular, and microvascular complications 14 , 23 . Previous Malaysian studies found that younger adults with T2D had poorer control of HbA1c, BP, and LDL-cholesterol 24 , 25 . Thus, there is a need to intensify metabolic control among this subpopulation to prevent adverse outcomes, especially after accounting for the legacy benefits of multifactorial risk interventions 26 .…”
Section: Discussionmentioning
confidence: 89%
“…We conducted secondary data analysis of a five-year retrospective open cohort of T2DM patients under the care of all public health clinics in Negeri Sembilan state, Malaysia, and the particulars had been previously published 4 , 19 , 20 . Negeri Sembilan is one of the sixteen states and federal territories in Malaysia and is located south of the capital city, Kuala Lumpur.…”
Section: Methodsmentioning
confidence: 99%
“…Negeri Sembilan is one of the sixteen states and federal territories in Malaysia and is located south of the capital city, Kuala Lumpur. The state was chosen due to its high prevalence of diabetes in Malaysia, potentially better data quality, and similar demographic characteristics and degree of urbanisation as the national average 4 , 5 , 19 . In an open cohort, patients could leave or be added over the study period, and this dynamic membership mirrored the real-world scenario 21 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations